52 Atrial Distension Index: An Echocardiographic Marker for Maintenance of Sinus Rhythm in Persistent AF Following DC Cardioversion. (6th June 2015) - Edroos, Sadat; Bayoumy, Amr; Simpson, Rupert; Owusu-Ansah, Alexander; El-Gendi, Hossam; Addawe, Mohamed; Mitrousi, Konstantina
Abstract : Introduction: Synchronised DC cardioversion is a commonly used treatment option for persistent atrial fibrillation (AF). Atrial distension is a predisposing factor for AF, and fibrosis of the atrial myocardium may prevent remodelling of the atrium to normalised parameters following cardioversion, with a fibrotic atrium begetting inevitable recurrence of AF. Methods: We retrospectively investigated echocardiographic appearances of 89 patients prior to elective DC cardioversion, to determine whether simple measurements of atrial dimensions in atrial systole and diastole may predict the recurrence of AF. We analysed 89 echocardiograms for patients attending for elective cardioversion, The long-term success following DC cardioversion at six months was correlated with patient demographics, biochemistry and parameters measured on echocardiogram. Results: 89 patients were assessed, with age 66.6 ± 1.0 years, ejection fraction 55.2 ± 1.2%, diameter (atrial diastole) 4.6 ± .0.1, and diameter (atrial systole) 4.1 ± 0.1. Left atrial diameter in atrial diastole, and atrial distension index, derived from measurements of atrial diameter in atrial systole and diastole on M-mode parasternal long axis view, were shown to have a statistically significant correlation with successful sustained sinoversion on linear regression (F(2, 83), p = 0.0176). Atrial distension index = [diameter (atrial diastole) – diameter (atrial systole)]/diameter (atrial systole). Conclusion: In summary atrial distension index, derived from simple measurements of the left atrium in systole and diastole from 2D transthoracic echocardiography, may predict persistence of sinus rhythm following DC cardioversion in persistent AF.